The use of acupuncture in Veterinary Medicine for small animals (canines) (Research, Society and Development, 2025)
Acupuncture, an ancient practice of Traditional Chinese Medicine, has gained ground in veterinary medicine as an effective complementary therapy in the treatment of various diseases. This technique works by stimulating specific points on the body, called acupoints, with the aim of promoting energy balance, pain relief, functional improvement, and accelerated clinical recovery. In Brazil, its veterinary use expanded from the 1980s onwards, driven by figures such as Professor Tetsuo Inada, and has been gaining increasing acceptance among professionals and pet owners, demonstrating a transformation in the approach to animal care. This study focused on evaluating the effectiveness of acupuncture in dogs, through the analysis of case reports published between 2021 and 2025. The methodology adopted was a literature review, with 17 scientific articles selected from platforms such as Google Scholar and SciELO, considering only studies with a detailed description of the use of the technique in dogs and excluding those involving other species. The technique has also demonstrated effectiveness in cases resistant to conventional medicine, and can be combined with other integrative therapies such as moxibustion, laser therapy, and ozone therapy. Although the studies present methodological limitations such as a small number of cases, lack of a control group, and diversity in protocols, the findings have relevant practical application, contributing to the development of more precise therapeutic protocols and consolidating acupuncture as a safe, accessible, and effective alternative. Its incorporation into conventional care expands treatment possibilities and promotes animal well-being, reinforcing its role in current veterinary medicine.